Using the ADDIE Model to Nurture the Development of Teachers’ CALL Professional Knowledge - Hui-Chin Yeh; Sheng-Shiang Tseng (Educational Technology & Society, 2019)
Although teacher training programs can deliver knowledge of ways to integrate technology into English as a Foreign Language (EFL) lessons, teachers may not achieve sustainable improvement in their Computer Assisted Language Learning (CALL) professional knowledge as they cannot not reflect on the effectiveness of their lessons through actual practice. This study contributes to the literature by illustrating how the integration of the ADDIE model with teachers’ lesson design influenced their CALL professional knowledge. Six EFL teachers participated in an 18-week course in which they designed, delivered, and revised a CALL lesson based on the ADDIE model. Results showed that the teachers demonstrated significant improvement in their CALL professional knowledge. The contextual analysis facilitated the teachers’ development of pedagogical knowledge by re-examining the current English teaching and learning issues. Through lesson design, the teachers reported that they could move away from traditional printed textbook instruction and paper-and-pencil tests to the computer-assisted language instruction, thus sharpening their online searching skills using open educational resource tools for English teaching. The implementation and evaluation of the lessons was valuable for teachers to evaluate their lessons by observing students’ learning behaviors and performance, which elevated teachers’ confidence in the use of computer-assisted language instruction for English teaching.